Marriage, Political Alliance, and Imperial Polities in Early Ghaznavid History. Issue 1 (April 2023) - Auer, Blain
Abstract : This article considers how marriages were utilized in early Ghaznavid history to forge political alliances, establish relationships of power and to bind together different royal family households. Marriage was employed as a diplomatic tool to ease political tensions and to strengthen coalitions. The Ghaznavid ruler Maḥmūd (r. 388–421/998–1030) utilized marriage alliances with great success to consolidate and expand his territories. In 391/1001, he forged a coalition with the Karakhanids through a marriage to the daughter of Naṣr b. ʿAlī (d. 403/1012–3). In 406/1015–16, Maḥmūd married his own sister Ḥurra Kāljī to the Khwarazmshah al-Maʾmūn II (r. 399–407/1009–17). This paper attempts to answer unstudied questions concerning the role of marriage and the influence of female royal family members in the construction of imperial polities of the medieval period in Central Asia, Iran, and Afghanistan. It shows that the effective creation of strategic marriage alliances was a key factor in the success of the early Ghaznavid empire.